Phenomenological inquiry: bridging subjective experience and objective health research - Roslan, Rika (Nanyang Technological University, 2025)
In the field of medicine, EBM dominates the sphere of health research. EBM claims that RCT is the “gold standard” of research. Meta-analysis of RCT and RCT research ranks high on the evidence hierarchy while qualitative research ranks low. However, this claim seems undue as it neglects many other aspects that are important to medicine such as patient variability and subjective experience. Phenomenology which focuses on the study on lived experience can add on to these weakness by employing a pluralistic approach. As such, phenomenology can serve as the bridge between integrating subjective experience and objective health research.